Application of Hydroinformatic Tools for Reservoirs Discharges Rules Assessment During a Flood Event - Pinho, José L. S. (2018)
Hydrological and hydrodynamic models are valuable tools for understanding complex river hydrodynamics behavior during flood events. These tools have been applied to develop a detailed study of the flood event occurred between 9 and 11 January 2016 in the river Mondego basin, causing severe floods at Coimbra city (Portugal). The study included the characterization of the operational discharge schemes of three upstream dams with direct influence on flow rates in the river basin, and the runoff flows from contributing catchments. A detailed analysis on hydrodynamic water levels at the flooded areas influenced by the operation of a downstream dam and the local river morphodynamics was performed. Hydroinformatic tools were applied in different scenarios allowing the characterization and identification of the key factors responsible for the flood event and contributing to emphasize the need to comply with the established rules for the discharges at the upstream dams during flood events